Academic researchers on the project market in the ethos of knowledge capitalism. (November 2017) - Brunila, Kristiina; Hannukainen, Kristiina
How knowledge capitalism retools the scope of academic research and researchers is an issue which this article ties to the project market in the ethos of knowledge capitalism. In Finland, academic research has been forced to apply for funding in project-based activities reflecting European Union policies. The project market, which in this article represents knowledge capitalism, shapes opportunities related to research and knowledge as well as in terms of researcher subjectivity. However, a critical approach that recognises the function of power can both highlight and challenge the forms of knowledge capitalism that reorganises the scope of research and researchers today.